Atividade antifúngica de extratos de plantas medicinais em amostras de Candida albicans isoladas de mucosa bucal - Danielle Leticia da Silva (2009)
Yeasts of the genus Candida does part of the indigenous human microbiota. However, they can behave as opportunistic pathogens, depending of host and fungal factors. The study of virulence factors of th e fungus becomes important to an understanding of its pathogenicity and development of antifungal drugs. A study was conducted in order to evaluate the antifungal activity of extracts of S. terebinthifolius and P. granatum in C. albicans . The minimum inhibitory concentration for S. terebinthifolius was on average 33.40 ug/ml, while for P. granatum was 59.77 ug/ml. Both extracts had fungistatic activity upon C. albicans. The treatments with extracts of S. terebinthifolius and P. granatum increasedyeasts hydrophobicity respectively by 14.22% and 33.23%. However, this increase was not significant in relation to control. The extra ct of S. terebinthifolius inhibited the adherence of yeasts to buccal epithelial cells in 29.59%, and this inhibition was statistically significant in relation to the untreat ed control (P <0.05). Despite the inhibition of 29.59% of adhesion, the treatment with extract of P. granatum was not more efficient than control in reducing the adhesion . Despite the different values obtained in two methods of biofilm quantification (crystal violet and XTT), in both itwas possible to verify that plant extracts didn't in hibit significantly the pre-formed biofilms. The analysis of the morphology of the biofilms showed that the extract of S. terebinthifolius reduced pseudo-hyphae formation, while the extract of P. granatum didnt cause changes to it. Both extracts didn't cause DNA fragmentation.